PENGEMBANGAN THEORY OF PLANNED BEHAVIOR PADA KEPUTUSAN PEMBELIAN GREEN PRODUCT - Nikmah, Masfiatun; Hartini, Sri (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This study aims to develop Theory of planned behavior. In this study added the variable Perceive Value (Gren value and Functional value) on the proposed model. Design/methodology/approach- this study was conducted with a survey of male consumers who use skincare. 200 samples were taken by purposive sampling. The analysis technique used is SEM smart PLS. Findings- The results of this study, of the 6 hypotheses were accepted 5 hypotheses and 1 hypothesis was rejected. This result shows that the green value and functional value have a significant positive effect on attitude toward green products. Likewise with Functional Value. This variable has a significant positive effect on the intention to purchase green products. Perceive behavior control does not moderate the relationship between attitude toward green products and intention to purchase green products. Keywords: green value, functional value, Attitude, purchase intention, Behaviour control